Penyuluhan PHBS dan memperagakan cara menggosok gigi yang baik dan benar serta cara mencuci tangan menggunakan sabun - Aminatus Sholikah; Shinta Wulandari; Amelia Amelia; Irma Tiara Rizki (JOURNAL OF Public Health Concerns, 2023)
Background: PHBS (Clean and Healthy Living Behavior) is very important to do, so that healthy life can be carried out properly. Therefore, everyone must be able to apply clean and healthy living behavior into daily life. Purpose: This counseling is to motivate children about the importance of doing PHBS in their daily life. Method: activities that we carry out in the form of counseling and assistance with lecture methods, as well as practice. With the theme of clean and healthy behavior (PHBS), namely how to brush teeth properly and correctly and carry out how to wash hands using soap. Results: The results of the program showed that they were able to know how to brush their teeth properly and correctly and how to wash their hands with soap. Conclusion: students are expected to be able to apply PHBS (Clean and Healthy Life Behavior) in their daily lives well.